Investigation of Temperature and Aging Effects in Nanostructured Dye Solar Cells Studied by Electrochemical Impedance Spectroscopy. (4th October 2009) - Toivola, Minna; Halme, Janne; Peltokorpi, Lauri; Lund, Peter
Abstract : Effects of aging and cyclically varying temperature on the electrical parameters of dye solar cells were analyzed with electrochemical impedance spectroscopy. Photoelectrode total resistance increased as a function of time due to increasing electron transport resistance in theTiO 2 film. On the other hand, photoelectrode recombination resistance was generally larger, electron lifetimes in theTiO 2 were film longer, and charge transfer resistance on the counter electrode was smaller after the temperature treatments than before them. These effects correlated with the slower deterioration rate of the temperature-treated cells, in comparison to the reference cells.